Evaluation of liver fibrosis in HCV-infected patients using two-dimensional shear-wave elastography (2D-SWE) before and after antiviral treatment - Inglot Marcin; Pozowski Patryk; Misiak Paula; Fleischer-Stępniewska Katarzyna; Lewandowski Łukasz; Bilski Mateusz; Zaleska-Dorobisz Urszula (Journal of Ultrasonography)
Chronic hepatitis C virus infections can lead to liver fibrosis. Appropriate treatment of chronic hepatitis C may result in significant fibrosis reversal. The best method to assess liver fibrosis is an invasive hepatic biopsy. Among non-invasive options, one of the most recent methods is two-dimensional shearwave elastography, which allows real-time visualization of liver stiffness. The purpose of this study was to analyze changes in liver fibrosis among patients with hepatitis C virus receiving direct-acting antiviral therapy.